Presence of a dog reduces subjective but not physiological stress responses to an analog trauma - Lass-Hennemann, Johanna; Peyk, Peter; Streb, Markus; Holz, Elena; Michael, Tanja (Frontiers in Psychology, 2014)
Dogs are known to have stress and anxiety reducing effects. Several studies have shown that dogs are able to calm people during cognitive and performance stressors. Recently, therapy dogs have been proposed as a treatment adjunct for PTSD patients. In this study we aimed to investigate, whether dogs also have anxiety- and stress reducing effect during “traumatic stressors”. 80 healthy female participants were randomly assigned to one of 4 conditions. They were exposed to a “traumatic” film clip (trauma-film-paradigm). For one group of participants a friendly dog was present during the film, one group of participants was accompanied by a friendly human, another control group watched the film with a toy animal and the last group watched the film clip alone. Participants that were accompanied by the dog during the film reported lower anxiety ratings and less negative affect after the film clip as compared to the “toy dog group” and the “alone group”. Results of the “dog group” were comparable to the group that was accompanied by a friendly human. There were no differences in physiological stress responses between the four conditions. Our results show that dogs are able to lessen subjectively experienced stress and anxiety during a “traumatic” stress situation. This effect was comparable to that of social support by a friendly person. Implications for PTSD patients are discussed.